Tax fraud as the most severe form of tax evasion: Review of legislation and practice in Serbia - Dimić Suzana (Faculty of Law, Niš, 2021)
Bearing in mind that taxation reduces disposable income, taxpayers' resistance to tax compliance is quite understandable. For this reason, the contemporary financial theory and practice pay special attention to the popularization of taxes, with special reference to the purpose of taxation. Taxes are acceptable to taxpayers insofar as they are used for funding public goods which are at the disposal of taxpayers as beneficiaries. Unlike other criminal offenses, where the detrimental effect may be directly visible, the immediate detrimental effect of tax offenses is not transparent. It generates a significant problem: there is a psychological effect that tax offences cause little or negligible social danger, which cannot be accepted as true. In effect, tax offenses entail very harmful and socially dangerous conduct because they threaten the fiscal interests of the state. Timely payment of taxes and other dues ensures continuity in financing public needs and provide for the proper functioning of the state. In case of tax evasion, or tax fraud as its most aggravated form, the state is deprived of the amount of revenue that would have been collected had all taxpayers abided by their tax liability. This paper focuses on the normative framework in the Republic of Serbia and the basic issues arising in practice, which are the result of the long-standing lenient penal policy of Serbian courts and numerous problems encountered in tax evasion proceedings (ranging from difficulties in conducting a financial investigation to the judges' professional competences and relevant knowledge to adjudicate cases in this field). In view of the harmful consequences for the fiscal system of the state, the question arises whether tax evasion and tax fraud have been relevantly criminalized in Serbian legislation. It seems that the latest amendments, which have increased the census (the amount of evaded tax) for the existence of this crime, will entail "moving away" from an adequate condemnation of such socially unacceptable conduct. This can only adversely affect the already low level of tax morale in Serbia.